Microbial community composition and functional potential in Annelida from abyssal and hadal zones of the Aleutian trench - Candace J. Grimes; Anthony M. Bonacolta; Kenneth M. Halanych (Progress in Oceanography, 2026)

Benthic community heterogeneity on the Eastern Antarctic continental shelf - Candace J. Grimes; Andrew R. Mahon; Kyle B. Donnelly; William Farris; Madison Gott; Coral Halanych; Conor Judge; Harrison I. Mancke; Nusrat J. Noor; Samantha A. Schreiter; Lindsay Uzarski; Jessica R. Zehnpfennig; et al. (Polar Biology, 2025)

Single nucleotide polymorphism data reveals distinct geographic structuring in the Antarctic circumpolar sea spider Nymphon australe - Jessica R. Zehnpfennig; Matthew P. Galaska; Kenneth M. Halanych; Andrew R. Mahon (Marine Biology, 2024)

Phylogenomic reconstruction influenced by assembly and annotation parameters: Using whole genome data to unravel the relationships of Spionidae (Annelida) - Viktoria E. Bogantes; Karin Meiβner; Damien S. Waits; Kevin M. Kocot; Kenneth M. Halanych (Zoologica Scripta, 2024)
Most efforts at improving accuracy in phylogenomic reconstructions have focused on improving tree‐building methods or orthology determination. Even though the use of whole genome sequence or transcriptome data is increasing, the degree to which accurate genome assembly and annotation influence phylogenetic inference has not been well explored. Here, we use low‐coverage whole genome sequencing of spionid annelids to explore the impact of different assemblers and annotation strategies on tree reconstruction. We also produce a phylogenetic hypothesis that spans the breadth of Spionidae, examining the current systematics of the group, which is based on morphological parsimony analyses and classical taxonomy. Our results show that both assembly and annotation can have important consequences for the pool of loci that may be available for tree reconstruction. When an identical phylogenomic pipeline is used, differences in assembly and annotation can account for variation in reconstructed topologies. Interestingly, the completeness and depth of the data used for training annotation software (i.e. data from model systems) appear to be more important, by some measures, than the degree of phylogenetic relatedness of the organism from which training data are drawn. Despite variation in recovered topologies, the recognised subfamily Spioninae is nested within Nerininae, suggesting that diagnostic characters of Nerininae (e.g. thick egg membrane, short‐headed sperm) are symplesiomorphies of Spionidae rather than apomorphies of a particular subclade. With the increased use of genomic data, our results advocate for a broader consideration of how assembly and annotation may impact data matrices used in phylogenomic analyses.

Nereididae (Annelida) phylogeny based on molecular data - Paulo R. Alves; Kenneth M. Halanych; Edson P. Silva; Cinthya S. G. Santos (Organisms Diversity & Evolution, 2023)

Metabarcoding analysis of meiobenthic biodiversity along the Gulf of Mexico continental shelf - Pamela M. Brannock; Amanda W.J. Demopoulos; Stephen C. Landers; Damien S. Waits; Kenneth M. Halanych (Estuarine, Coastal and Shelf Science, 2023)

Community structure along the Western Antarctic continental shelf and a latitudinal change in epibenthic faunal abundance assessed by photographic surveys - Candace J. Grimes; Kyle Donnelly; Cheikhouna Ka; Nusrat Noor; Andrew R. Mahon; Kenneth M. Halanych (Frontiers in Marine Science, 2023)
The Southern Ocean’s continental shelf communities harbor high benthic biodiversity. However, most census methods have relied on trawling or dredging rather than direct observation. Benthic photographic and videographic transect surveys serve a key role in characterizing marine communities’ abundance and diversity, and they also provide information on the spatial arrangement of species within a community. To investigate diversity and abundance in Southern Ocean benthic communities, we employed photographic transects during cruises aboard the RVIB Nathanial B. Palmer (November 2012) and the ASRV Laurence M. Gould (February 2013). One kilometer long photographic transects were conducted at 8 sites along 6,000 km of Western Antarctica from the tip of the Antarctic Peninsula to the Ross Sea from which epifaunal echinoderms, tunicates, arthropods, cnidarians, poriferans, and annelids were identified and counted allowing estimations of biodiversity. Our results do not support a latitudinal trend in diversity, but rather a decrease in abundance of macrofaunal individuals at higher latitude sites. All communities sampled on the Western Antarctic shelf were primarily dominated by ophiuroids, pycnogonids, holothuroids, and demosponges. However, the most abundant taxon across all sites was Ophionotus victoriae , followed by the symbiotic partners Iophon sp. (demosponge) and Ophioplinthus spp. (ophiuroid). Data also confirm that the Southern Ocean is composed of discretely unique benthic communities. These results provide critical understanding of the current community structure and diversity serving as a baseline as the Antarctic continental shelf changes due to rising ocean temperatures, climate change, and collapse of large ice sheets.

Corrigendum: Diversity, Distribution and Phylogeny of Hesionidae (Annelida) Colonizing Whale Falls: New Species of Sirsoe and Connections Between Ocean Basins - Mauricio Shimabukuro; Orlemir Carrerette; Joan Manel Alfaro-Lucas; Alexandra Elaine Rizzo; Kenneth M. Halanych; Paulo Yukio Gomes Sumida (Frontiers in Marine Science, 2021)

Spatial proximity between polyploids across South American frog genera - Kyle T. David; Kenneth M. Halanych (Journal of Biogeography, 2021)
Aim Polyploids have been theorized to occur more frequently in environments that are subjected to severe conditions or sudden disruptions. Here we test the expectation that polyploid taxa occur more frequently in extreme or disrupted environments than their diploid counterparts, whether due to increased adaptive potential, environmental resilience or cross‐ploidy competition. Location South America. Taxon All frog genera in the area with both polyploid and diploid member species ( Ceratophrys, Chiasmocleis, Odontophrynus, Phyllomedusa and Pleurodema ). Methods In all, 13,556 occurrence records of 82 frog species were collected from the Global Biodiversity Information Facility. Species distribution models, range overlap estimates, statistical tests and principal component analyses were used to estimate and compare environments between diploid and polyploid species within and across genera using several categorical and quantitative variables taken from multiple publicly available sources. Results Almost all polyploid occurrences are found within southeastern South America, largely to the exclusion of diploids. Polyploid species occur more closely with intergeneric polyploids than they do with congeneric diploids. Southeastern South America is more temperate, seasonal and less forested when compared to the tropical environments more commonly inhabited by diploids. The habitat ranges of polyploid species are subject to greater temperature fluctuations than diploid species. This region has also experienced major transformations in the modern era, owing to an agriculture boom over the last century. Polyploid occurrences are more likely to be found in areas with greater cropland usage, fertilizer application and pesticide application than diploids. Main Conclusions Across species, temperature seasonality was the only variable with strong statistical differences between diploids and polyploids. Greater annual fluctuations in temperature may lead to more established polyploid species due to reasons mentioned above; however, extreme temperature differences are also known to contribute to polyploid gamete formation, providing a possible non‐selective explanation. Polyploid occurrences are also more likely to be found in areas of high agricultural impact, providing support for the hypothesis that polyploids are more resilient to environmental disruptions than diploids.

Summary of Findings and Research Recommendations from the Gulf of Mexico Research Initiative - Charles Wilson; Michael Feldman; Michael Carron; Nilde Dannreuther; Kenneth Halanych; Jennifer Petitt; Jürgen Rullkötter; Paul Sandifer; Kevin Shaw; John Shepherd; David Westerholm; Callan Yanoff; et al. (Oceanography, 2021)
Following the Deepwater Horizon explosion and oil spill in 2010, the Gulf of Mexico Research Initiative (GoMRI) was established to improve society’s ability to understand, respond to, and mitigate the impacts of petroleum pollution and related stressors of the marine and coastal ecosystems. This article provides a high-level overview of the major outcomes of the scientific work undertaken by GoMRI. This initiative contributed to significant knowledge advances across the physical, chemical, geological, and biological oceanographic research fields, as well as in related technology, socioeconomics, human health, and oil spill response measures. For each of these fields, this paper outlines key advances and discoveries made by GoMRI scientists (along with a few surprises), synthesizing their efforts in order to highlight lessons learned, future research needs, remaining gaps, and suggestions for the next generation of scientists.

Effects of Petroleum By-Products and Dispersants on Ecosystems - Kenneth Halanych; Cameron Ainsworth; Erik Cordes; Richard Dodge; Markus Huettel; Irving Mendelssohn; Steven Murawski; Claire Paris-Limouzy; Patrick Schwing; Richard Shaw; Tracey Sutton (Oceanography, 2021)
Gulf of Mexico (GOM) ecosystems are interconnected by numerous physical and biological processes. After the Deepwater Horizon (DWH) disaster, these ecological processes facilitated dispersal of oil-spill toxicants or were damaged and broken. A considerable portion of post-DWH research focused on higher levels of biological organization (i.e., populations, communities, and ecosystems) spanning at least four environments (onshore, coastal, open ocean, and deep benthos). Damage wrought by the oil spill and mitigation efforts varied considerably across ecosystems. Whereas all systems show prolonged impacts because of cascading effects that impacted functional connections within and between communities, deep-sea and mesopelagic environments were particularly hard hit and have shown less resilience than shallow environments. In some environments, such as marshes or the deep-sea benthos, products from the spill are still biologically accessible. Some shallow ecosystems show signs of recovery, and populations of some species show resilience; however, a return to a “pre-spill” state is questionable. Importantly, habitats in which large amounts of energy flow through the ecosystem (marshes, coastal regions) recovered more quickly than low energy habitats (deep-sea benthos). Functional interactions between Gulf of Mexico systems are more complex and widespread than generally recognized. Moreover, ecosystems in the Gulf are subject to multiple stressors that can combine to impart greater, and less predictable, impacts. To help mitigate the effects of future insults, we identified four salient areas of research that should be addressed for each of the major environments within the GOM: establishing monitoring systems; quantifying coupling between GOM ecosystems; developing criteria for assessing the “vulnerability” and “resilience” of species, communities, and ecosystems; and developing holistic predictive modeling.

Impacts of Petroleum, Petroleum Components, and Dispersants on Organisms and Populations - Steven Murawski; Martin Grosell; Cynthia Smith; Tracey Sutton; Kenneth Halanych; Richard Shaw; Charles Wilson (Oceanography, 2021)
Following the Deepwater Horizon blowout, oil, degraded oil, oil mixed with dispersants, and management responses to the spill affected a variety of Gulf of Mexico organisms. This review provides examples of various documented impacts, common patterns, and trends across organisms and/or their environments, and discusses future implications as well as directions for future research. Organism effects are generally characterized as lethal and sublethal. Sublethal can be short term, long term, or permanent and multigenerational. We present individual examples of effects on behavioral response, olfaction, vision, cardiac function, and gene shift, based on research done in laboratories, mesocosm settings, and the field. Future research should emphasize collection and analysis of routine toxicological baselines and examine how and if molecular impacts cascade up to populations. This research will require development of rapid molecular tools and testing procedures to determine exposure compared to field-relevant exposure levels and to be able to extrapolate laboratory results to the field, especially given the mosaic of differing contaminant concentrations (below, at, or exceeding critical concentrations that result in lethal or sublethal effects) occurring in the environment. Recent chemical studies have identified a detectable suite of polycyclic aromatic hydrocarbon metabolites for which there are no toxicity data; further research is needed to determine their impacts on food webs.

GoMRI Insights into Microbial Genomics and Hydrocarbon Bioremediation Response in Marine Ecosystems - Shannon Weiman; Samantha Joye; Joel Kostka; Kenneth Halanych; Rita Colwell (Oceanography, 2021)
The Deepwater Horizon oil spill represents one of the most damaging environmental catastrophes of our generation. It contaminated vast areas of the open ocean, the deep sea, and the shoreline of the Gulf region and disrupted its ecosystems, with both residual and long-term impacts. At the core of all of these ecosystems are microbial communities that perform essential biogeochemical processes and ecosystem services such as carbon and nutrient cycling. Despite their importance, relatively little was known about marine microbes that degrade hydrocarbons in the Gulf of Mexico prior to the Deepwater Horizon spill, nor the effect of hydrocarbons on the microbiology of the Gulf region. Research carried out through the Gulf of Mexico Research Initiative (GoMRI) revealed cooperative microbial communities operating at the heart of bioremediation services with highly adaptive and complex dynamics. In addition, these efforts established new methods for assessing and monitoring ecosystem health, whereby microbial population genetics can serve as indicators of biogeochemical disruptions and/or restoration status in marine and coastal environments. Although much research is still needed to fully understand and engage microbially mediated bioremediation services, GoMRI constructed a strong foundation of methods, discoveries, and overarching principles to build upon. These insights and tools will help scientists better prepare for, and respond to, future environmental catastrophes, from oil tanker spills to long-term disruptions of climate change.

Considerations for Scientists Getting Involved in Oil Spill Research - Kenneth Halanych; David Westerholm (Oceanography, 2021)
From the outset of the Deepwater Horizon (DWH) oil spill, scientists from many different sectors (e.g., government, industry, academia, independent) sprang into action to establish appropriate experimental procedures, collect essential samples, and gather meaningful data. The scale of the spill and the unprecedented use of dispersants challenged scientists familiar with oil spill research, but also drew in many scientists new to hydrocarbon studies. The response to DWH, as with other oil spills, was centered on environmental and human safety concerns as mandated by the US Clean Water Act, the Oil Pollution Act of 1990, and the National Contingency Plan, which defines roles and responsibilities of multiple parties. These roles, however, are usually carried out by government, industry, or government-contracted researchers and until DWH have included limited input from academic investigators. In studying the DWH spill, most researchers also had to navigate the logistics and liability issues that can be associated with an oil spill event, including the formal government response processes that can be unfamiliar to academic researchers. In particular, biological researchers had to rapidly educate themselves on the nuances and complexity of the hydrocarbons and dispersants throughout the water column. Nonetheless, biological studies were hampered by the lack of controls or challenges with employing experimental approaches in the field. DWH spill research also highlighted challenges and opportunities that arose due to the interactions of researchers from the academic, government, and industry sectors. The objective of this document is to provide some perspective and to highlight issues that researchers new to the area should consider when approaching oil spill and dispersant studies.

Phylogenomic analyses reveal a Palaeozoic radiation and support a freshwater origin for clitellate annelids - Christer Erséus; Bronwyn W. Williams; Kevin M. Horn; Kenneth M. Halanych; Scott R. Santos; Samuel W. James; Michel Creuzé des Châtelliers; Frank E. Anderson (Zoologica Scripta, 2020)
Clitellata is a major clade of Annelida comprising nearly all freshwater and terrestrial annelids as well as several marine species. We investigated clitellate phylogenetic relationships using transcriptomes sampled from 74 taxa (64 clitellates and 10 polychaetes), including multiple representatives of nearly all major clitellate higher taxa (Branchiobdellida, Capilloventridae, Crassiclitellata, Enchytraeidae, Haplotaxidae, Hirudinida, Lumbriculida, Moniligastridae, Naididae, Parvidrilidae, Phreodrilidae, Propappidae and Randiellidae). We used a number of filtered data matrices and phylogenetic analyses to examine the effects of data partitioning, missing data and compositional and branch‐length heterogeneity and used the resulting phylogenies for divergence time estimation and ancestral habitat reconstructions. All analyses and filtering methods produced a consistent, strongly supported topology in which (a) Enchytraeidae, Hirudinida, Hirudinea (here, Branchiobdellida plus Hirudinida), Lumbriculida, Lumbriculata (Lumbriculida plus Hirudinea), Phreodrilidae and Naididae are monophyletic, (b) a Parvidrilidae + Randiellidae clade is sister to the rest of Clitellata, (c) Phreodrilidae is sister to Naididae, (d) Haplotaxidae is non‐monophyletic, with some haplotaxids grouping with Crassiclitellata + Moniligastridae, (e) the Phreodrilidae + Naididae clade is sister to all other clitellates except Parvidrilidae + Randiellidae and Capilloventridae, and (f) Lumbriculata is sister to the Crassiclitellata + Moniligastridae + Haplotaxidae (in part) clade. Ancestral habitat reconstructions and divergence time analysis suggested that the most recent common ancestor of Clitellata lived in freshwater during the Devonian (419–359 million years ago) and that all major extant clitellate lineages arose over the next ~150 million years, with multiple lineages subsequently returning to marine habitats or invading land. This study provides a phylogenetic framework for further investigation of the geological, environmental and biotic forces and genomic changes that may have impacted clitellate evolution and enabled several major habitat transitions within this group.

A mesopelagic ctenophore representing a new family, with notes on family-level taxonomy in Ctenophora: Vampyroctena delmarvensis gen. nov. sp. nov. (Vampyroctenidae, fam. nov.) - James P. Townsend; Michael G. Tassia; Alejandro Damian-Serrano; Nathan V. Whelan; Kenneth M. Halanych; Alison M. Sweeney (Marine Biodiversity, 2020)

The phylogeny of Nereididae (Annelida) based on mitochondrial genomes - Paulo Ricardo Alves; Kenneth M. Halanych; Cinthya Simone Gomes Santos (Zoologica Scripta, 2020)
Nereididae comprises a diverse group of marine worms and is one of the most studied families in Annelida. However, phylogenetic relationships within the group are still poorly understood. Previous studies, based on morphological data, have disagreed on the membership of recognized subfamilies and, current taxonomy lacks sufficient phylogenetic underpinning. This study uses complete mitochondrial genome and transcriptome data to evaluate relationships within Nereididae and test currently employed subfamilies. Ancestral state reconstructions were performed to evaluate if morphological traits found in the pharynx, that is papillae and paragnaths, correspond with phylogenetic relationships based on mitochondrial data. Our results suggest that Nereidinae and Gymnonereidinae, as currently recognized, are not monophyletic groups. In general, molecular results suggest that morphological features used in nereidid taxonomy need re‐evaluation as they may be more evolutionary plastic than recognized. Ancestral state reconstruction suggests that papillae and paragnaths may have evolved early in the family and their presence, as currently employed in taxonomy, does not allow accurate diagnose of groups within Nereididae. In contrast, unique mitochondrial gene order defines at least one higher‐level clade within Nereididae.

Unrecognized diversity of a scale worm, Polyeunoa laevis (Annelida: Polynoidae), that feeds on soft coral - Viktoria E. Bogantes; Nathan V. Whelan; Katelynn Webster; Andrew R. Mahon; Kenneth M. Halanych (Zoologica Scripta, 2020)
A goal of taxonomy is to employ a method of classification based on phylogeny that captures the morphological and genetic diversity of organismal lineages. However, morphological and genetic diversity may not always be concordant, leading to challenges in systematics. The scale worm Polyeunoa laevis has been hypothesized to represent a species complex based on morphology, although there is little knowledge of its genetic diversity. Commonly found in Antarctic waters and usually associated with gorgonian corals (especially Thouarella ), this taxon is also reported from the south‐west Atlantic, Magellanic and sub‐Antarctic regions. We employ an integrative taxonomic approach to examine the traditional morphological characters used for scale worm identification in combination with COI mitochondrial gene data and whole mtDNA genomes. Moreover, we consider P. laevis' s association with Thouarella by examining data from the mMutS gene, a soft‐coral phylogenetic marker. Analyses for P. laevis recovered 3 clades, two in Antarctic waters and one from the Argentina‐Indian Ocean. Interestingly, genetic and morphological results show differences between specimens from South Argentina and the Antarctic region, suggesting that open ocean barriers might have limited gene flow from these regions. Bayesian phylogenetic analyses for Thouarella resulted in at least 12 lineages, although some of the lineages consist of only a single individual. Our results show different evolutionary histories for both species, confirming that association between these scale worms and their hosts is not restrictive. For both taxonomic groups, biodiversity in the Southern Ocean appears to be underestimated.

Diversity, Distribution and Phylogeny of Hesionidae (Annelida) Colonizing Whale Falls: New Species of Sirsoe and Connections Between Ocean Basins - Mauricio Shimabukuro; Orlemir Carrerette; Joan Manel Alfaro-Lucas; Alexandra Elaine Rizzo; Kenneth M. Halanych; Paulo Yukio Gomes Sumida (Frontiers in Marine Science, 2019)
Whale falls are important environments contributing to biodiversity, connectivity and evolutionary novelty in deep-sea ecosystem. Notwithstanding, most of this knowledge is based in studies from NE Pacific basin. Interestingly, the only known natural whale fall on the SW Atlantic has faunal composition affinities with carcasses from other deep-ocean basins. In this carcass, annelid worms belonging to Hesionidae are abundant and species-rich, and include some shared species with NE Pacific Ocean. Here we evaluate the diversity of Hesionidae on the SW Atlantic using new information of implanted whale bones and explore whether some species have interbasin distribution or if they represent cryptic species in different basins. We described, using morphological and molecular data, a total of 10 new hesionid species and report of a new lineage Sirsoe ‘BioSuOr,’ not formally described herein. Two hesionids found exclusively in deep-sea chemosynthetic environments, Sirsoe Pleijel (1998) and Vrijenhoekia Pleijel et al. (2008) , are primarily distinguished from each other by the presence of a median antenna on the former and its absence on the latter. However, our analyses showed that Vrijenhoekia should be synonymized with Sirsoe and for this reason we emended the diagnosis of Sirsoe. We also emphasized the presence of Sirsoe balaenophila comb. nov. and S. sirikos in SW Atlantic whale falls confirming their interbasin distribution. Moreover, COI and 16S rDNA data reveal that S. balaenophila comb. nov. also comprises cryptic species on the SW Atlantic ( S. pirapuan sp. nov. and S. ypupiara sp. nov) and perhaps also in the Pacific Ocean (herein named as S. balaenophila lineage-2). The new species, S. maximiano , is shared between whale falls from SW Atlantic and vent sites from Mid-Cayman Spreading Center. Our data adds to the growing literature showing species are shared between deep ocean basins and among cognate deep-sea environments. Zoobank registration publication LSID - urn:lsid:zoobank.org:pub:7E891B1D-DCE4-45C8-83F4-8586D286B327.

Riverscape genetic variation, migration patterns, and morphological variation of the threatened Round Rocksnail, Leptoxis ampla - Nathan V. Whelan; Matthew P. Galaska; Breanna N. Sipley; Jennifer M. Weber; Paul D. Johnson; Kenneth M. Halanych; Brian S. Helms (Molecular Ecology, 2019)
Within riverine systems, headwater populations are hypothesized to harbour higher amounts of genetic distinctiveness than populations in the main stem of a river and display increased genetic diversity in large, downstream habitats. However, these hypotheses were mostly developed with insects and fish, and they have not been tested on many invertebrate lineages. Pleuroceridae gastropods are of particular ecological importance to rivers of eastern North America, sometimes comprising over 90% of macroinvertebrate biomass. Yet, virtually nothing is known of pleurocerid landscape genetics, including whether genetic diversity follows predictions made by hypotheses developed on more mobile species. Moreover, the commonly repeated hypothesis that intraspecific morphological variation in gastropods results from ecophenotypic plasticity has not been well tested on pleurocerids. Using 2bRAD‐seq to discover single nucleotide polymorphisms, we show that the threatened, Cahaba River endemic pleurocerid, Leptoxis ampla, has limited gene flow among populations and that migration is downstream‐biased, conflicting with previous hypotheses. Both tributary and main stem populations harbour unique genomic profiles, and genetic diversity was highest in downstream populations. Furthermore, L. ampla shell morphology was more correlated with genetic differences among individuals and populations than habitat characteristics. We anticipate similar genetic and demographic patterns to be seen in other pleurocerids, and hypotheses about gene flow and population demographics that were based on more mobile taxa often, but not always, apply to freshwater gastropods. From a conservation standpoint, genetic structure of L. ampla populations suggests distinctive genetic diversity is lost with localized extirpation, a phenomenon common across the range of Pleuroceridae.

Spirorchis spp. (Digenea: Schistosomatoidea) infecting map turtles (Cryptodira: Emydidae: Graptemys spp.) in southeastern North America: A new species, molecular phylogenies, and key to species - Jackson R. Roberts; Micah B. Warren; Kenneth M. Halanych; Stephen A. Bullard (Systematic Parasitology, 2019)

Preface—biodiversity of Icelandic waters - Karin Meißner; Saskia Brix; Kenneth M. Halanych; Anna M. Jażdżewska (Marine Biodiversity, 2018)

Diversity and phylogenetic relationships of North Atlantic Laonice Malmgren, 1867 (Spionidae, Annelida) including the description of a novel species - Viktoria E. Bogantes; Kenneth M. Halanych; Karin Meißner (Marine Biodiversity, 2018)

A new genus and species of turtle blood fluke (Digenea: Schistosomatoidea) from the Mekong snail-eating turtle, Malayemys subtrijuga (Schlegel & Müller) (Testudines: Geoemydidae) in Vietnam, with a reassessment of related Asiatic turtle blood flukes and molecular phylogeny - Jackson R. Roberts; Cova R. Arias; Kenneth M. Halanych; Binh T. Dang; Stephen A. Bullard (Systematic Parasitology, 2018)

Phylogenomics of tubeworms (Siboglinidae, Annelida) and comparative performance of different reconstruction methods - Yuanning Li; Kevin M. Kocot; Nathan V. Whelan; Scott R. Santos; Damien S. Waits; Daniel J. Thornhill; Kenneth M. Halanych (Zoologica Scripta, 2017)
Deep‐sea tubeworms (Annelida, Siboglinidae) represent dominant species in deep‐sea chemosynthetic communities (e.g. hydrothermal vents and cold methane seeps) and occur in muddy sediments and organic falls. Siboglinids lack a functional digestive tract as adults, and they rely on endosymbiotic bacteria for energy, making them of evolutionary and physiological interest. Despite their importance, inferred evolutionary history of this group has been inconsistent among studies based on different molecular markers. In particular, placement of bone‐eating Osedax worms has been unclear in part because of their distinctive biology, including harbouring heterotrophic bacteria as endosymbionts, displaying extreme sexual dimorphism and exhibiting a distinct body plan. Here, we reconstructed siboglinid evolutionary history using 12 newly sequenced transcriptomes. We parsed data into three data sets that accommodated varying levels of missing data, and we evaluate effects of missing data on phylogenomic inference. Additionally, several multispecies‐coalescent approaches and Bayesian concordance analysis ( BCA ) were employed to allow for a comparison of results to a supermatrix approach. Every analysis conducted herein strongly supported Osedax being most closely related to the Vestimentifera and Sclerolinum clade, rather than Frenulata, as previously reported. Importantly, unlike previous studies, the alternative hypothesis that frenulates and Osedax are sister groups to one another was explicitly rejected by an approximately unbiased ( AU ) test. Furthermore, although different methods showed largely congruent results, we found that a supermatrix method using data partitioning with site‐homogenous models potentially outperformed a supermatrix method using the CAT ‐ GTR model and multispecies‐coalescent approaches when the amount of missing data varies in a data set and when taxa susceptible to LBA are included in the analyses.

An Opportunity to Inform and Educate Through the Gulf of Mexico Research Initiative: Outreach Efforts Surrounding the Deepwater Horizon Oil Spill - Debra Benoit; Leigh Zimmermann; Katie Fillingham; Stephen Sempier; Nilde Dannreuther; Jarryl Ritchie; Kenneth Halanych (Oceanography, 2016)

Introduction to the Special Issue: An Overview of the Gulf of Mexico Research Initiative - John Shepherd; Debra Benoit; Kenneth Halanych; Michael Carron; Rick Shaw; Chuck Wilson (Oceanography, 2016)

Metabarcoding reveals environmental factors influencing spatio‐temporal variation in pelagic micro‐eukaryotes - Pamela M. Brannock; Alice C. Ortmann; Anthony G. Moss; Kenneth M. Halanych (Molecular Ecology, 2016)
Marine environments harbour a vast diversity of micro‐eukaryotic organisms (protists and other small eukaryotes) that play important roles in structuring marine ecosystems. However, micro‐eukaryote diversity is not well understood. Likewise, knowledge is limited regarding micro‐eukaryote spatial and seasonal distribution, especially over long temporal scales. Given the importance of this group for mobilizing energy from lower trophic levels near the base of the food chain to larger organisms, assessing community stability, diversity and resilience is important to understand ecosystem health. Herein, we use a metabarcoding approach to examine pelagic micro‐eukaryote communities over a 2.5‐year time series. Bimonthly surface sampling (July 2009 to December 2011) was conducted at four locations within Mobile Bay (Bay) and along the Alabama continental shelf (Shelf). Alpha‐diversity only showed significant differences in Shelf sites, with the greatest differences observed between summer and winter. Beta‐diversity showed significant differences in community composition in relation to season and the Bay was dominated by diatoms, while the Shelf was characterized by dinoflagellates and copepods. The northern Gulf of Mexico is heavily influenced by the Mobile River Basin, which brings low‐salinity nutrient‐rich water mostly during winter and spring. Community composition was correlated with salinity, temperature and dissolved silicate. However, species interactions (e.g. predation and parasitism) may also contribute to the observed variation, especially on the Shelf, which warrants further exploration. Metabarcoding revealed clear patterns in surface pelagic micro‐eukaryote communities that were consistent over multiple years, demonstrating how these techniques could be greatly beneficial to ecological monitoring and management over temporal scales.

How our view of animal phylogeny was reshaped by molecular approaches: lessons learned - Kenneth M. Halanych (Organisms Diversity & Evolution, 2016)

Evolution of Sulfur Binding by Hemoglobin in Siboglinidae (Annelida) with Special Reference to Bone-Eating Worms, Osedax - Damien S. Waits; Scott R. Santos; Daniel J. Thornhill; Yuanning Li; Kenneth M. Halanych (Journal of Molecular Evolution, 2016)

Diversity and distribution within the sea spider genus Pallenopsis (Chelicerata: Pycnogonida) in the Western Antarctic as revealed by mitochondrial DNA - Avril M. Harder; Kenneth M. Halanych; Andrew R. Mahon (Polar Biology, 2016)

Reconstruction of Cyclooxygenase Evolution in Animals Suggests Variable, Lineage-Specific Duplications, and Homologs with Low Sequence Identity - Justin C. Havird; Kevin M. Kocot; Pamela M. Brannock; Johanna T. Cannon; Damien S. Waits; David A. Weese; Scott R. Santos; Kenneth M. Halanych (Journal of Molecular Evolution, 2015)

Depth-dependent gene flow in Gulf of Mexico cold seep Lamellibrachia tubeworms (Annelida, Siboglinidae) - Dominique A. Cowart; Kenneth M. Halanych; Stephen W. Schaeffer; Charles R. Fisher (Hydrobiologia, 2014)

Reconciling taxonomy and phylogeny in the bristleworm family E unicidae (polychaete, A nnelida) - Joana Zanol; Kenneth M. Halanych; Kristian Fauchald (Zoologica Scripta, 2014)
Eunicid annelids inhabit diverse marine habitats worldwide, have ecological and economic importance and have been pictured in the news as giant predator worms. They compose a traditional stable taxon recently supported as monophyletic but characterized by plesiomorphies. Most genera within the family have been recovered as paraphyletic in previous studies. We present a phylogenetic hypothesis for eunicid based on molecular ( COI , 16S rDNA , 18S rDNA ) and morphological data (213 characters), including an explicit attempt to account for serial homology. Eunicidae as well as monophyletic genera M arphysa sensu stricto and L ysidice is redefined based on synapomorphies. N ematonereis is synonymized to L ysidice . L eodice and N icidion are resurrected to name monophyletic groups including species previously included in E unice and M arphysa sensu lato . Traditional diagnostic characters such as the absence/presence of peristomial cirri, lateral antennae and branchiae are homoplasies and not informative at the generic level. Different coding of traditional characters (i.e. articulation of prostomial appendages) and novel characters of prostomial features and regionalization of the body support the monophyly of the family and genera level clades. Thus, the phylogenetic hypothesis presented here and the evolution of characters provided background information for taxonomic changes yielding evolutionary meaningful classification and diagnoses for the family and genera.

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

Seeing stars: a molecular and morphological investigation into the evolutionary history of Odontasteridae (Asteroidea) with description of a new species from the Galapagos Islands - Alexis M. Janosik; Kenneth M. Halanych (Marine Biology, 2013)

Erratum to: Evolutionary history of Southern Ocean Odontaster sea star species (Odontasteridae; Asteroidea) - Alexis M. Janosik; Andrew R. Mahon; Kenneth M. Halanych (Polar Biology, 2012)

Evolutionary history of Southern Ocean Odontaster sea star species (Odontasteridae; Asteroidea) - Alexis M. Janosik; Andrew R. Mahon; Kenneth M. Halanych (Polar Biology, 2011)

Molecules reject an opheliid affinity for Travisia (Annelida) - CHRISTIANE PAUL; KENNETH M. HALANYCH; RALPH TIEDEMANN; CHRISTOPH BLEIDORN (Systematics and Biodiversity, 2010)

Phylogeography of the Antarctic planktotrophic brittle star Ophionotus victoriae reveals genetic structure inconsistent with early life history - Rebecca L. Hunter; Kenneth M. Halanych (Marine Biology, 2010)

Origins of holopelagic Typhloscolecidae and Lopadorhynchidae within Phyllodocidae (Phyllodocida, Annelida) - Torsten H. Struck; Kenneth M. Halanych (Zoologica Scripta, 2010)

Range shifts and species diversity in marine ecosystem engineers: patterns and predictions for European sedimentary habitats - Sarah K. Berke; Andrew R. Mahon; Fernando P. Lima; Kenneth M. Halanych; David S. Wethey; Sarah A. Woodin (Global Ecology and Biogeography, 2010)
Aim Ecosystem engineering polychaetes in the genus Diopatra are undergoing range shifts in western Europe. Here we: (1) assess the species diversity underlying these shifts; (2) link biogeographic patterns to sea surface temperature patterns; and (3) predict possible ecosystem‐level outcomes of Diopatra 's northward expansion. Location Western Europe. Methods We use molecular phylogenetic and morphological evidence to assess species diversity and biogeographic ranges. Using regression tree analyses, we assess thermal limits for two Diopatra species. We compare biogeographic patterns with historical sea surface temperature patterns to draw links between range shifts and climate change. Finally, we review published data to predict potential ecological changes as Diopatra invades new habitats. Results The native Diopatra neapolitana range has contracted 130 km to the south. A cryptogenic species, Diopatra sp. A, has extended the northern limit of the genus 350 km to the southern Brittany Peninsula. Both shifts can be explained by historical sea surface temperature anomalies. The Diopatra sp. A expansion is predicted to continue into the English Channel and the North Sea, introducing large tube structures to sheltered sedimentary habitats that currently lack such structures. Main conclusions As climate change intensifies, the sediment‐stabilizing Diopatra sp. A will invade habitats dominated by the bioturbating lugworm Arenicola marina . The resulting interaction between functionally different ecosystem engineers will probably cause ecological changes in northern European coastal waters. Existing data for Diopatra species and arenicolids suggest that the diversity and biomass of macroalgae, vascular plants, infauna and epibenthic fauna may increase, while microbial activity may decrease. Net changes in productivity will depend on the relative rates of these changes.

DNA uncovers Antarctic nemertean biodiversity and exposes a decades-old cold case of asymmetric inventory - Andrew R. Mahon; Daniel J. Thornhill; Jon L. Norenburg; Kenneth M. Halanych (Polar Biology, 2010)

Discrete genetic boundaries of three Streblospio (Spionidae, Annelida) species and the status of S. shrubsolii - Andrew R. Mahon; Heidi K. Mahon; Daniel M. Dauer; Kenneth M. Halanych (Marine Biology Research, 2009)

Ocean barriers and glaciation: evidence for explosive radiation of mitochondrial lineages in the Antarctic sea slug Doris kerguelenensis (Mollusca, Nudibranchia) - NERIDA G. WILSON; M. SCHRÖDL; KENNETH M. HALANYCH (Molecular Ecology, 2009)
Strong currents and deep passages of water can be barriers for larval dispersal of continental marine animals, but potential effects on direct developers are under‐investigated. We examined the genetic structure of Doris kerguelenensis , a directly developing sea slug that occurs across the Drake Passage, the body of water separating Antarctica from South America. We found deep mitochondrial divergences within populations on both sides of the Drake Passage, and South American animals formed multiple sister‐group relationships with Antarctic animals. A generalised molecular clock suggested these trans‐Drake pairs diverged during the Pliocene–Pleistocene, after the formation of the Drake Passage. Statistical parsimony methods recovered 29 separate haplotype networks (many sympatric) that likely correlate with allopatric events caused by repeated glacial cycles. Data from 16S were congruent but more conserved than COI, and the estimated ancestral 16S haplotype was widespread. The marked difference in the substitution rates between these two mitochondrial genes results in different estimates of connectivity. Demographic analyses on networks revealed some evidence for selection and expanding populations. Contrasting with the Northern Hemisphere, glaciation in Antarctica appears to have increased rather than reduced genetic diversity. This suggests orbitally forced range dynamics based on Northern Hemisphere phylogeography do not hold for Antarctica. The diverse lineages found in D. kerguelenensis point towards a recent, explosive radiation, likely reflecting multiple refuges during glaciation events, combined with limited subsequent dispersal. Whether recognised as cryptic species or not, genetic diversity in Antarctic marine invertebrates appears higher than expected from morphological analyses, and supports the Antarctic biodiversity pump phenomenon.

Open‐ocean barriers to dispersal: a test case with the Antarctic Polar Front and the ribbon worm Parborlasia corrugatus (Nemertea: Lineidae) - DANIEL J. THORNHILL; ANDREW R. MAHON; JON L. NORENBURG; KENNETH M. HALANYCH (Molecular Ecology, 2008)
Open‐ocean environments provide few obvious barriers to the dispersal of marine organisms. Major currents and/or environmental gradients potentially impede gene flow. One system hypothesized to form an open‐ocean dispersal barrier is the Antarctic Polar Front, an area characterized by marked temperature change, deep water, and the high‐flow Antarctic Circumpolar current. Despite these potential isolating factors, several invertebrate species occur in both regions, including the broadcast‐spawning nemertean worm Parborlasia corrugatus . To empirically test for the presence of an open‐ocean dispersal barrier, we sampled P. corrugatus and other nemerteans from southern South America, Antarctica, and the sub‐Antarctic islands. Diversity was assessed by analyzing mitochondrial 16S rRNA and cytochrome c oxidase subunit I sequence data with Bayesian inference and tcs haplotype network analysis. Appropriate neutrality tests were also employed. Although our results indicate a single well‐mixed lineage in Antarctica and the sub‐Antarctic, no evidence for recent gene flow was detected between this population and South American P. corrugatus . Thus, even though P. corrugatus can disperse over large geographical distances, physical oceanographic barriers (i.e. Antarctic Polar Front and Antarctic Circumpolar Current) between continents have likely restricted dispersal over evolutionary time. Genetic distances and haplotype network analysis between South American and Antarctic/sub‐Antarctic P. corrugatus suggest that these two populations are possibly two cryptic species.

Toward a mechanistic understanding of larval dispersal: insights from genomic fingerprinting of the deep‐sea hydrothermal vent tubeworm Riftia pachyptila - Timothy M. Shank; Kenneth M. Halanych (Marine Ecology, 2007)
Larval dispersal is critical for the maintenance of species populations in patchy and ephemeral hydrothermal vent habitats. On fast‐spreading ridges, such as the East Pacific Rise, rates of habitat turnover are comparable to estimated lifespans of many of the inhabiting species. Traditionally, dispersal questions have been addressed with two very different approaches, larval studies and population genetics. Population genetic studies of vent‐endemic species have been informative for determining whether patterns of dispersal are suggestive of stepping stone or island models and estimating rates of gene flow (effective migrants per generation) over broad geographic ranges. However, these studies leave fundamental questions unanswered about the specific mechanisms by which larvae disperse and species maintain their populations and biogeographic ranges. With the goal of examining genetic structure and elucidating alternative larval dispersal mechanisms, we employed a genomic DNA fingerprinting technique, amplified fragment length polymorphisms (AFLPs). To assess the potential utility of AFLPs, and genetic structure of the hydrothermal vent tubeworm Riftia pachyptila , genomic ‘fingerprints’ were recovered from 29 individuals from five vent fields spanning a distance of up to c. 5000 km along the East Pacific Rise. In contrast to previous population genetic studies that found little to no genetic structure using allozymes and mitochondrial DNA, genetic analyses of 630 polymorphic AFLP loci identified distinct subclades within R. pachyptila populations. Significant levels of differentiation were observed among populations from all vent regions as well as within each region. Discrete assemblages of tubeworms separated by as little as c. 400 m within a given vent region were genetically distinguishable and cohorts (based on size‐frequency distribution) within an aggregation were found to be most closely related. These results suggest that mechanisms of larval dispersal act to retain cohort fidelity in R. pachyptila .

Molecular phylogeny of siboglinid annelids (a.k.a. pogonophorans): a review - Kenneth M. Halanych (Hydrobiologia, 2005)

Test of the monophyly of Odostomiinae and Turbonilliinae (Gastropoda, Heterobranchia, Pyramidellidae) based on 16S mtDNA sequences - Christoffer Schander; Kenneth M. Halanych; Thomas Dahlgren; Per Sundberg (Zoologica Scripta, 2003)
Schander, C., Halanych, K. M., Dahlgren, T. & Sundberg, P. (2003) Test of the monophyly of Odostomiinae and Turbonilliinae (Gastropoda, Heterobranchia, Pyramidellidae) based on 16S mtDNA sequences. — Zoologica Scripta, 32 , 243−254. While gastropod phylogeny has received much recent attention, relationships within some major gastropod clades have still not been studied. The Pyramidellidae is one such group, comprising more than 6000 named species in more than 350 genera. We sequenced part of the mitochondrial 16S gene from 32 species in an attempt to clarify pyramidellid phylogeny and employed a successive alignment approach that allowed us to maximize the phylogenetic signal of the data. Neighbour‐joining, maximum parsimony and likelihood analyses recovered two distinct clades. One clade consisted of Noemiamea which nested within Odostomia ( sensu stricto ) . The inclusion of Brachystomia , Megastomia , Jordaniella and Liostomia within Odostomia is not supported. The second clade comprised Spiralinella , Brachystomia , Boonea , Jordaniella , Liostomia and Parthenina . Our results further suggest that Turbonilla, as interpreted by most authors, is polyphyletic. This study shows that the 16S gene is useful in unravelling pyramidellid phylogeny but needs to be combined with other data (including molecular, morphological and developmental) to fully clarify the evolutionary relationships.

Siboglinid evolution shaped by habitat preference and sulfide tolerance - Anja Schulze; Kenneth M. Halanych (Hydrobiologia, 2003)